Redundant Path Optimization in Smart Ship Software-Defined Networking and Time-Sensitive Networking Networks: An Improved Double-Dueling-Deep-Q-Networks-Based Approach - Yanli Xu; Songtao He; Zirui Zhou; Jingxin Xu (Journal of Marine Science and Engineering)
Traditional network architectures in smart ship communication systems struggle to efficiently manage the integration of heterogeneous sensor data. Additionally, conventional end-to-end transmission algorithms that rely on single-metric and single-path selection are inadequate in fulfilling the high reliability and real-time transmission requirements essential for high-priority service data. This inadequacy results in increased latency and packet loss for critical control information. To address these challenges, this study proposes an innovative ship network framework that synergistically integrates Software-Defined Networking (SDN) and Time-Sensitive Networking (TSN) technologies. Central to this framework is the introduction of a redundant multipath selection algorithm, which leverages Double Dueling Deep Q-Networks (D3QNs) in conjunction with Graph Convolutional Networks (GCNs). Initially, an optimization function encompassing transmission latency, bandwidth utilization, and packet loss rate is formulated within a software-defined time-sensitive network transmission framework tailored for smart ships. The proposed D3QN-GCN-based algorithm effectively identifies optimal working and redundant paths for TSN switches. These dual-path configurations are then disseminated by the SDN controller to the TSN switches, enabling the TSN’s inherent reliability redundancy mechanisms to facilitate the simultaneous transmission of critical service flows across multiple paths. Experimental evaluations demonstrate that the proposed algorithm exhibits robust convergence characteristics and significantly outperforms existing algorithms in terms of reducing network latency and packet loss rates. Furthermore, the algorithm enhances bandwidth utilization and promotes balanced network load distribution. This research offers a novel and effective solution for shipboard switch path selection, thereby advancing the reliability and efficiency of smart ship communication systems.